Preparation method of self-repairing anti-aging automobile original factory varnish
Through three-stage graphene surface modification treatment and ball milling refinement, the shortcomings of existing original automotive varnishes in self-repair and aging resistance are solved, and high-performance, environmentally friendly and long-life coating effects are achieved.
Patent Information
- Application Number
- CN202411587801.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-14
AI Technical Summary
The existing original automotive varnish has shortcomings in self-repair and aging resistance, especially in terms of high costs, short service life and environmental pollution.
Three-stage graphene surface modification treatment includes wetting graphene with a specific solvent combination, adding surfactant for surface functionalization, and stabilizing the dispersed state of graphene through superdispersant, and finally making the graphene particle size reach D50 by ball milling. ≤2μm.
It improves the dispersion and compatibility of graphene, improves the mechanical properties and aging resistance of the coating, extends the service life, and reduces the negative impact on the environment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular to a method for preparing self-repairing and aging-resistant automobile original varnish. Background Art
[0002] With the rapid development of the automobile industry and the increasing requirements of consumers for the appearance quality of vehicles, the requirements for environmental protection, high performance, multi-function and intelligence of automobile original varnish, as an important part of protecting the paint surface of vehicles and improving the appearance of vehicles, are becoming increasingly prominent. At present, the original automobile varnish on the market has certain limitations in terms of protection and aesthetic effects, especially in terms of self-repair and aging resistance, which have not been effectively solved.
[0003] Existing original car varnish usually needs to be self-repaired by applying a film, but this method is not only expensive, but also has a limited service life of only about 5 years. In addition, traditional varnish is prone to aging, color change and paint damage after long-term use in the face of environmental changes, which not only affects the appearance and protection of the car, but also causes a certain degree of pollution to the environment.
[0004] Therefore, it is particularly important to develop a new type of self-repairing and aging-resistant automotive original varnish. This new type of varnish is required to provide long-term stable aging resistance and self-repairing functions while maintaining high performance and environmental protection, thereby effectively reducing maintenance costs, extending the service life of the varnish, and reducing negative impacts on the environment. Summary of the invention
[0005] The purpose of the present invention is to solve the above problems in the prior art and to provide a method for preparing a self-repairing and aging-resistant automobile original varnish.
[0006] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing a self-repairing anti-aging automobile original varnish comprises the following steps:
[0007] S1 Three-stage graphene surface modification treatment: First stage: put the mixed solvent into the constant temperature device, add graphene, start the constant temperature device, set the temperature of the constant temperature device to 60-70℃; use a magnetic stirring device to carry out the first stirring operation;
[0008] The mixed solvent includes N-methylpyrrolidone, butyl acetate and diethylene glycol butyl ether; according to the weight ratio, N-methylpyrrolidone: butyl acetate: diethylene glycol butyl ether is 50-60: 20-30: 20-30;
[0009] The graphene is a single-layer graphene powder, the graphene single-layer rate is not less than 80%, the graphene diameter D50 is 5-10μm, the graphene purity is not less than 99%, the graphene defect density ratio is not more than 0.3, the graphene carbon oxygen ratio is not less than 25; the graphene specific surface area is not less than 2630m 2 / g
[0010] The second stage: after the first stirring operation is completed, a surfactant is added and a second stirring is continued using a magnetic stirring device; the surfactant is phospholipid-polyethylene glycol-silane;
[0011] The third stage: after the second stirring operation is completed, the dispersant is added dropwise by a peristaltic pump, and the third stirring operation is continued by a magnetic stirring device. After the stirring is completed, a modified graphene mixture is obtained; the dispersant is specifically SUP1360 super dispersant;
[0012] According to the weight ratio, the mixed solvent: graphene: surfactant: hyperdispersant is 96-98: 0.5-1: 0.5-1: 1-2;
[0013] The three-stage graphene surface modification process is a key technology that provides a basis for the application of graphene in self-repairing and anti-aging automotive original varnish. The specific functions of this step are as follows:
[0014] Improving the dispersibility of graphene: In the first stage, graphene is treated with a mixed solvent of N-methylpyrrolidone, butyl acetate and diethylene glycol butyl ether. This specific solvent combination can effectively wet graphene and increase its dispersibility in the solvent.
[0015] Surface functionalization: In the second stage, the added phospholipid-polyethylene glycol-silane surfactant can react with the graphene surface, introducing functional groups to change its surface properties. This surface modification not only further enhances the dispersibility of graphene, but also improves its compatibility with the resin matrix, which is crucial for the function of graphene and the optimization of the final coating performance.
[0016] Stable dispersion effect: In the third stage, the dispersion state of graphene in the mixed solvent can be effectively stabilized by adding SUP1360 hyperdispersant and high-speed stirring. This treatment ensures the uniform distribution of graphene and prevents re-agglomeration that may occur during long-term storage or handling.
[0017] Improve the final coating performance: The application of graphene in the coating after three-stage surface modification will help improve the mechanical properties and aging resistance of the coating. At the same time, its good dispersibility ensures the integrity and appearance quality of the coating.
[0018] The surfactant is phospholipid-polyethylene glycol-silane (DSPE-PEG silane), which is a surface active phospholipid PEG-based compound that can be used to modify graphene surfaces. The PEG linker bridges the DSPE and silane groups to provide a better, flexible linker structure and enhanced reactivity. The silane groups on this molecule are highly reactive to graphene. The molecular weight of the polyethylene glycol is 1000.
[0019] SUP1360 superdispersant has a strong viscosity reduction effect and is suitable for the dispersion and stabilization of graphene. SUP1360 prevents the dispersed graphene particles from re-flocculation through steric hindrance and prevents the system from sedimentation.
[0020] Magnetic stirring equipment was selected because it provides uniform and gentle stirring, which is essential to maintain the integrity and uniform mixing of materials.
[0021] The temperature was set at 60-70°C to optimize the activity of the surfactant and dispersant while preventing thermal degradation of the material.
[0022] The weight ratio is set as follows: mixed solvent: graphene: surfactant: hyperdispersant is 96-98: 0.5-1: 0.5-1: 1-2. This ratio is designed to ensure that graphene can be adequately suspended in the solvent and fully coated by the surfactant and dispersant. A higher solvent ratio helps with initial dispersion and suspension, while an appropriate amount of surfactant and dispersant can effectively improve the surface properties of graphene and enhance its compatibility and stability in the substrate material.
[0023] Physical and chemical properties of graphene require:
[0024] Single-layer graphene powder: The single-layer rate is not less than 80%, which ensures the efficient energy conversion and conductivity of graphene. Single-layer graphene has higher surface activity and reactivity, which makes it easier to form a reinforced interaction with the resin substrate.
[0025] Graphene diameter and purity: The requirements of D50 of 5-10μm and purity of not less than 99% ensure that the graphene has a higher surface area and fewer impurities, which contributes to its uniform distribution in the resin and excellent functional performance.
[0026] Defect Density and Carbon-Oxygen Ratio: A defect density ratio of no more than 0.3 and a carbon-oxygen ratio of no less than 25 ensure the structural integrity and chemical stability of graphene. These parameters indicate the quality and suitability of graphene, especially in high-performance coatings, where these properties are critical to achieving long-term durability and self-healing capabilities.
[0027] Strict requirements for graphene quality are the key to ensuring that the final automotive original paint has excellent self-healing and aging resistance. These design details directly affect the application effect and durability of the coating and are an important part of product quality control.
[0028] S2 refinement: placing the modified graphene mixture in a ball mill, adding ball milling media, and starting ball milling. During the ball milling process, sampling is performed to detect the particle size until D50 ≤ 2 μm, thereby obtaining a graphene dispersion.
[0029] The reasons for D50≤2μm are as follows:
[0030] 1. Enhanced dispersibility: Graphene with small particle size is easier to disperse evenly in the resin matrix. Graphene with larger particle size tends to form agglomerates, which can lead to uneven physical properties in the coating, such as uneven surface and inconsistent mechanical properties. Reducing the particle size to 2μm or less can significantly improve its uniformity and stability in the coating.
[0031] 2. Improve mechanical strength and durability: Finer graphene particles can be better embedded in the resin substrate, forming a stronger chemical and physical bond with the substrate material. This enhanced bonding helps improve the overall mechanical properties of the coating, such as hardness, scratch resistance and flexibility.
[0032] 3. Optimize self-healing function: The nanoscale of graphene can enhance its interaction with other components in the resin, especially in terms of self-healing function. Nanoscale graphene can interact with self-healing resins to promote faster response and repair of damaged areas because they can respond faster to external stimuli (such as temperature changes) and trigger repair mechanisms.
[0033] 4. Improve visual and aesthetic performance: In the coating industry, the particle size has a direct impact on the smoothness and gloss of the final product. Smaller particle size can make the coating smoother and glossier, thereby improving the appearance quality of the product.
[0034] Therefore, in the process of preparing self-repairing and anti-aging automotive original varnish, ball milling to reduce the graphene particle size to D50 ≤ 2μm is an important step to ensure product performance and quality. This is not only related to the mechanical and chemical properties of the coating, but also affects the appearance and long-term durability of the coating.
[0035] S3 prepares the base paint: according to the weight ratio, ethylene glycol butyl ether, n-butanol and propylene glycol methyl ether acetate are put into the mixer to carry out the first stirring operation. After the first stirring operation, the self-repairing PU resin and the solvent-based self-repairing resin are added in sequence to carry out the second stirring operation. After the second stirring operation is completed, the stirring speed is increased to carry out the third stirring operation. During the stirring process of the third stirring operation, the graphene dispersion, the ultraviolet light absorber, the light stabilizer, the anti-shrinkage flow control agent, the leveling agent are added in sequence. The agent and the conductive agent are stirred for the fourth time, and after stirring evenly, a base paint is obtained; according to the weight ratio, ethylene glycol butyl ether: n-butanol: propylene glycol methyl ether acetate: self-repairing PU resin: solvent-based self-repairing resin: graphene dispersion: ultraviolet light absorber: light stabilizer: anti-shrinkage flow control additive: leveling agent: conductive agent is 2-5:2-5:1-3:50-60:25-35:2-4:1-3:0.5-1:0.2-0.3:0.2-0.3:0.2-0.3;
[0036] The self-repairing PU resin is specifically L-2960 self-repairing PU resin; the solvent-based self-repairing resin is specifically TRE-2-S2 solvent-based self-repairing resin; the ultraviolet light absorber is specifically Tinuvin 1130 ultraviolet light absorber; the light stabilizer is specifically Tinuvin 292 light stabilizer; the anti-shrinkage flow control additive is specifically EFKA-3600 additive; the leveling agent is specifically EFKA FL3750 leveling agent; the conductive agent is specifically BYK ES80 conductive agent;
[0037] S4: preparing a strengthening curing agent: adding butyl acetate, methyl isobutyl ketone, and propylene glycol methyl ether acetate to a mixer in sequence to perform a first stirring operation; after the first stirring operation is completed, adding N3390 curing agent, and performing a second stirring operation, after the second stirring operation is completed, a strengthening curing agent mixture is obtained;
[0038] According to the weight ratio, butyl acetate: methyl isobutyl ketone: propylene glycol methyl ether acetate: N3390 curing agent is 15-20: 10-15: 5-10: 60-70;
[0039] S5: preparing a flow regulating solvent: adding butyl acetate, diacetone alcohol, methyl isobutyl ketone and propylene glycol methyl ether acetate into a mixer and stirring them to obtain a flow regulating solvent after stirring them evenly;
[0040] According to the weight ratio, butyl acetate: diacetone alcohol: methyl isobutyl ketone: propylene glycol methyl ether acetate is 50-60: 15-20: 15-25: 10-15;
[0041] S6 homogenization: mixing and stirring the base paint, the strengthening curing agent mixture and the flow regulating solvent to obtain the original automobile varnish;
[0042] According to the weight ratio, the base paint: the strengthening curing agent mixture: the flow regulating solvent is 3:1:0.2-0.5.
[0043] Preferably, in step S1, in the first stirring operation, the stirring speed is 200-300 r / min, and the stirring time is 30-40 minutes; in the second stirring operation, the stirring speed is 300-400 r / min, and the stirring time is 20-25 minutes; in the third stirring operation, the stirring speed is 700-900 r / min, and the stirring time is 20-25 minutes.
[0044] Preferably, in step S2, the ball mill is a vertical ball mill, the operating speed of the vertical ball mill is 1800-2000r / min, the ball milling medium is any one of stainless steel beads, ceramic beads and cemented carbide beads, and the diameter of the ball milling medium is 0.8-1.2mm.
[0045] Preferably, in step S3, in the first stirring operation, the stirring speed is 300-400 r / min, and the stirring time is 5-10 minutes; in the second stirring operation, the stirring speed is 300-400 r / min, and the stirring time is 5-10 minutes; in the third stirring operation, the stirring speed is 800-1000 r / min.
[0046] Preferably, in step S3, L-2960 self-healing PU resin forms an interpenetrating network structure system through a cross-linking reaction between the PU resin and the isocyanate; the parameters are as follows: viscosity (CPa.s / 25°C, CPS): 30-120CPS; solid content: 55% ± 2%; OH value (solid): 130mgKOH / g; OH% (solid): 3.8; acid value (solid): 2-5mgKOH / g; the solvent is butyl acetate;
[0047] The parameters of TRE-2-S2 solvent-based self-healing resin are as follows: viscosity (25°C): 450mPa.s; hydroxyl acrylic resin solid content: 70%; hydroxyl value: 116mgKOH / g; solvent: butyl acetate;
[0048] Tinuvin 1130 UV absorber parameters are as follows: ingredients include benzotriazole; dynamic viscosity at 20°C is 7400mPa.s; density at 20°C is 1.17g / cm 3 ;
[0049] The parameters of Tinuvin292 light stabilizer are as follows: the ingredients include 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and bis(1,2,2,6,6-pentamethylpiperidinol) sebacate; the dynamic viscosity at 20°C is 400cps; the density at 20°C is 1.02kg / m3 ;
[0050] The ingredients of EFKA-3600 additive are 100% fluorocarbon molecular compounds;
[0051] The composition of EFKA FL 3750 leveling agent is 100% acrylate copolymer;
[0052] The parameters of BYK ES80 conductive agent are as follows: ingredient composition: alkyl alcohol ammonium salt solution of unsaturated carboxylic acid ester; amine value: 140 mgKOH / g; acid value: 140 mgKOH / g; density (20°C): 1.01 g / ml; solvent: isobutanol.
[0053] Preferably, in step S4, in the first stirring operation, the stirring speed is 300-400 r / min, and the stirring time is 5-10 minutes; in the second stirring operation, the stirring speed is 600-800 r / min, and the stirring time is 10-20 minutes.
[0054] Preferably, in step S4, the parameters of the N3390 curing agent are as follows: type: hexamethylene diisocyanate trimer; supply form: 90% butyl acetate / 100 solvent naphtha (1:1) solution; NCO content: 19.6%±0.3%; non-volatile component: 90%±1%; viscosity: 550±150mPa.s; color value at 23°C ≤40; HDI monomer <0.15%.
[0055] Preferably, in the stirring operation in step S5, the stirring speed is 300-400 r / min, and the stirring time is 5-10 minutes.
[0056] The selection of ethylene glycol butyl ether, n-butyl alcohol and propylene glycol methyl ether acetate as solvents is of great significance. These solvents not only affect the film-forming properties of the coating, but also have a significant effect on the applicability and durability of the final product. The following are several key reasons for using these specific solvents:
[0057] 1. Solubility and compatibility:
[0058] Ethylene glycol butyl ether: It has excellent solubility and can effectively dissolve a variety of resins and additives. This solvent is often used to improve the fluidity and uniformity of the coating, help the uniform distribution of the coating during film formation, and reduce aggregation and unevenness in the coating.
[0059] n-Butanol: As an alcohol solvent, it increases the flexibility and crack resistance of the coating. The moderate evaporation rate of n-Butanol helps control the drying time and leveling of the coating, thereby improving the overall appearance and smoothness of the coating.
[0060] Propylene glycol methyl ether acetate: This is a reactive diluent with a slow volatilization rate, which can extend the open time of the paint and enable the paint to maintain suitable viscosity and fluidity for a longer period of time, which is beneficial for operators to carry out painting operations, especially when fine painting is required.
[0061] 2. Improve coating performance: The combination of these solvents helps to optimize the drying process of the coating and reduce surface defects such as orange peel and pinholes. Appropriate solvent evaporation can control the surface tension of the coating and improve the gloss and smoothness of the coating.
[0062] The stable volatilization process also ensures the uniformity of the chemical composition of the coating during the curing process, which is crucial to ensure the mechanical properties and weather resistance of the coating.
[0063] 3. Environmental and health impact: Selecting solvents with lower toxicity and higher flash points is also very important to meet environmental safety and health standards. The volatility of these solvents helps to reduce the concentration of harmful substances in the working environment and reduce potential threats to the health of operators.
[0064] 4. Chemical stability and compatibility: The chemical stability of these solvents ensures that they do not react undesirably with other chemical components in the coating, which is very important for maintaining the long-term performance and appearance of the coating.
[0065] Taking all the above factors into consideration, the use of ethylene glycol butyl ether, n-butyl alcohol and propylene glycol methyl ether acetate not only optimizes the processing and application process of the coating, but also helps to achieve better product performance and user experience. The selection of these solvents is based on their comprehensive benefits in improving product performance, operating convenience and environmental safety.
[0066] L-2960 self-healing PU resin plays a key role in the preparation of self-healing, aging-resistant automotive original varnish, mainly due to its unique chemical properties and performance characteristics that are highly matched to application requirements. The following are the main reasons for adopting this resin and the reasons for its parameter requirements: 1. Self-healing ability: L-2960 self-healing PU resin is a polyurethane (PU) resin with excellent self-healing properties. This resin can self-heal through molecular-level interactions after physical damage (such as scratches) to restore the original surface integrity and appearance. In automotive original varnish, this property is very important because it can significantly extend the service life of the coating and maintain the appearance of the car.
[0067] 2. Solid content and environmental adaptability: L-2960 self-healing PU resin has a solid content of 55% ± 2%. A higher solid content means less release of volatile organic compounds (VOCs) when the coating is cured, which is conducive to meeting environmental protection standards while ensuring the fullness and corrosion resistance of the coating.
[0068] 3. Chemical stability and interpenetrating network structure: The interpenetrating network structure is formed, which provides excellent chemical stability and mechanical strength, which is necessary for automotive exterior coatings. In addition, this structure can also provide better wear resistance and weather resistance at the macro and micro levels.
[0069] 4. Optimized rheology and processability: With a viscosity of 30-120 CPS, L-2960 resin is easy to process and apply, suitable for modern spraying equipment. Moderate viscosity also helps to evenly apply the coating and reduce dripping or sagging during the coating process.
[0070] 5. Reactivity: The OH value (hydroxyl value) of L-2960 resin is 130 mgKOH / g, which means it has high reactivity and can effectively react with the curing agent to form a strong cross-linked network. This high hydroxyl value is conducive to increasing the cross-linking density and enhancing the physical properties of the coating.
[0071] 6. Low acid value and long-term stability:
[0072] The acid value of 2-5 mgKOH / g indicates that L-2960 resin is relatively stable during storage and use, and is not prone to self-polymerization or degradation, which is crucial to maintaining the consistency and predictability of coating performance.
[0073] In summary, the chemical and physical properties of L-2960 self-healing PU resin make it very suitable for the preparation of self-healing anti-aging automotive original varnish. Its excellent self-healing ability, environmental protection characteristics, stable chemical properties and good processing performance together ensure the high quality and long-term durability of the coating product.
[0074] The application of TRE-2-S2 solvent-based self-healing resin in the preparation of self-healing, aging-resistant automotive original varnish is based on its unique chemical properties and significant contribution to coating performance. This resin provides excellent mechanical strength, durability and self-healing functions, making it an ideal choice in high-performance automotive coatings. The following is a detailed analysis of the reasons for using TRE-2-S2 resin and its parameter requirements: 1. High hydroxyl value: It has a hydroxyl value of 116 mgKOH / g, which is a key indicator for measuring its reactivity. A high hydroxyl value means that the resin contains more reactive hydroxyl groups, which can effectively react with the hexamethylene diisocyanate trimer in the reinforcing curing agent in step S4 to form a strong cross-linked network. This cross-linked network is essential for improving the mechanical properties, chemical resistance and wear resistance of the coating.
[0075] 2. Appropriate viscosity: The viscosity of TRE-2-S2 resin is 450mPa.s (at 25°C). This medium viscosity makes the resin easy to handle and apply, while maintaining good fluidity, which is conducive to uniform coating. Appropriate viscosity also helps to improve the overall appearance quality of the coating and reduce bubbles and other construction defects.
[0076] 3. High solid content: The solid content of TRE-2-S2 resin reaches 70%, which means that after the coating is cured, most of the resin components will remain in the coating, and only a small amount of solvent will evaporate. High solid content helps to reduce the volume loss of the coating during the curing process, improve the fullness and covering power of the coating, and reduce the emission of volatile organic compounds (VOC), which is more in line with environmental protection requirements.
[0077] 4. Good self-repairing function: Solvent-based self-repairing resins can restore their original properties through physical and chemical mechanisms after microscopic damage by introducing specific chemical groups into the molecular structure. This self-repairing function is very attractive for original automotive clearcoats because it can extend the life of the coating and reduce wear and scratches caused by daily use.
[0078] 5. Chemical compatibility: TRE-2-S2 resin has good compatibility with other coating ingredients (such as UV absorbers, light stabilizers and leveling agents), ensuring that the mixed coating system is stable without stratification or precipitation, thus ensuring the consistency and effect of the coating.
[0079] Combining the above characteristics, TRE-2-S2 solvent-based self-healing resin provides key technical support for the preparation of self-healing and aging-resistant automotive original varnish, meeting the dual requirements of modern automotive coatings for performance and environmental protection.
[0080] Specific chemicals Tinuvin 1130 UV absorber, Tinuvin 292 light stabilizer, EFKA-3600 anti-crater flow control additive, EFKA FL 3750 leveling agent and BYK ES80 conductive agent are used to ensure the performance and durability of the coating in various environments. The following are the reasons for the selection and parameter requirements of each material:
[0081] Tinuvin 1130 UV absorber: Ingredients: Includes benzotriazole, a highly efficient UV absorbing compound that absorbs a wide band of UV light, reducing chemical degradation caused by UV exposure. Dynamic viscosity and density: High viscosity helps maintain stable dispersion in the coating and is not easy to settle, and matching density helps the uniformity of the coating. Uses: Reduces light-induced aging, such as color change, photolysis and material performance degradation, thereby extending the service life of the original automotive clearcoat.
[0082] Tinuvin 292 Light Stabilizer: Composition: Contains a specific chemical structure that helps capture free radicals and slows down degradation caused by light and oxidation. Dynamic viscosity and density: Appropriate viscosity and density facilitate mixing and application during coating preparation and ensure uniformity of the coating. Uses: Enhances the light and weather resistance of the coating against the effects of light and heat in the external environment.
[0083] EFKA-3600 Anti-Pitting Flow Control Additive: Ingredients: Fluorocarbon molecular compounds, which are very effective in providing excellent surface tension regulation and help improve the appearance of the coating. Uses: Prevent craters and pinholes during the coating process and improve the overall quality and appearance of the coating.
[0084] EFKA FL 3750 leveling agent: Ingredients: Acrylate copolymer, can form a uniform film on the coating surface, providing good leveling properties. Uses: Improve the surface flatness and finish of the coating, and reduce the orange peel effect that may occur during the curing process of the coating.
[0085] BYK ES80 Conductive Agent: Ingredients: Alkyl alcohol ammonium salt solution of unsaturated carboxylic acid ester, this ingredient helps to improve the conductivity of the coating. Amine value and acid value: ensure chemical stability and compatibility, as well as reactivity in the coating. Density: compatible with other components, helps uniform application of the coating. Use: While providing antistatic properties, it also helps to reduce dust accumulation on the coating surface and improve the cleanliness and gloss of the coating.
[0086] These specific materials and parameters are selected based on their direct contribution to improving the performance, appearance, durability and environmental suitability of the final product.
[0087] In the preparation of self-repairing anti-aging automotive original paint, the proportions of each component are carefully designed to ensure the performance, appearance, durability and environmental adaptability of the final product. Here is a detailed analysis of the proportion of each component and why these proportions were chosen:
[0088] Ethylene glycol butyl ether, n-butyl alcohol and propylene glycol methyl ether acetate:
[0089] Purpose: These ingredients are mainly used as solvents to help other solid ingredients disperse evenly during mixing. These ratios (2-5:2-5:1-3) are selected mainly to adjust the evaporation rate and solvency of the solvent to ensure uniform drying and good fluidity of the coating.
[0090] Effect: Maintaining moderate viscosity of the coating, facilitating coating operations while ensuring drying speed and smoothness of the coating.
[0091] Self-healing PU resin and solvent-based self-healing resin: Use: These are the main resins of the coating, responsible for forming the structural basis of the coating and providing self-healing function. The ratio (50-60:25-35) ensures that the coating has sufficient mechanical strength and good self-healing properties.
[0092] Effect: The higher ratio of self-healing PU resin and solvent-based self-healing resin allows the coating to effectively self-heal after damage, extending its service life.
[0093] Graphene dispersion: Use: As a reinforcing agent to improve the mechanical properties and conductivity of the coating, it also has the function of converting solar energy into thermal energy. This ability enables graphene to accelerate the thermodynamic reaction of the surrounding self-healing resin when receiving sunlight, thereby promoting the rapid recovery of damaged areas; the ratio (2-4) is sufficient to achieve the desired enhancement effect without excessively affecting other properties of the coating. The conjugated structure composed of carbon atoms on graphene can just match the energy of ultraviolet rays, thereby effectively absorbing and shielding ultraviolet rays.
[0094] UV absorbers, light stabilizers, anti-crater flow control agents, leveling agents and conductive agents: Uses: These additives are used to protect the coating from UV light damage, enhance the weather resistance of the coating, improve the surface quality of the coating and increase conductivity. The ratio (1-3:0.5-1:0.2-0.3:0.2-0.3:0.2-0.3) is carefully adjusted according to the functional requirements and interactions of each component.
[0095] Effect: These proportions ensure a coating with an optimal balance of protection, aesthetics and functionality.
[0096] In summary, these carefully designed ratios are designed to optimize the comprehensive performance of the coating, ensuring that the coating provides self-healing functions while also having excellent aging resistance and environmental adaptability. The proportion of each component is designed to maximize its unique contribution while maintaining the synergistic effect of the overall formulation.
[0097] In the process of preparing self-repairing and anti-aging automotive original varnish, it is crucial to choose the right curing agent and corresponding solvent, because these ingredients directly affect the curing speed, final performance and ease of application of the coating. The specific analysis is as follows: 1. Selected curing agent and solvent:
[0098] Butyl acetate: It is a commonly used solvent with good solubility and moderate volatilization rate. It helps dissolve the resin and curing agent, while controlling the drying time of the coating to ensure that the coating can dry evenly during the curing process.
[0099] Methyl isobutyl ketone: This solvent has a strong solvency and can effectively dissolve a variety of chemicals, including some poorly soluble curing agents, thereby enhancing the mixing uniformity of the curing agent and the base material.
[0100] Propylene glycol methyl ether acetate: As a slow evaporating solvent, it can extend the open time of the coating, thereby allowing the hardener to be more evenly distributed in the coating and reducing the possibility of defects in the coating.
[0101] N3390 curing agent: It is a trimer of hexamethylene diisocyanate with a high NCO content, which gives it better cross-linking ability and can improve the mechanical strength and chemical resistance of the coating. The high NCO content of this curing agent is conducive to reacting with the hydroxyl groups in the coating to form a highly cross-linked network structure, which is crucial to improving the wear resistance and self-healing ability of the coating.
[0102] 2. Reasons for weight ratio selection:
[0103] Butyl acetate (15-20%): As the main part of the solvent, it is enough to keep the curing agent and other components in a good dissolved state while controlling the drying speed of the coating.
[0104] Methyl isobutyl ketone (10-15%): It is used in a moderate proportion to enhance the overall solubility of the solvent mixture and ensure that the curing agent can be completely dissolved in the substrate.
[0105] Propylene glycol methyl ether acetate (5-10%): Lower proportions are sufficient to adjust the drying speed and flow of the coating without negatively affecting the drying time and coating quality.
[0106] N3390 curing agent (60-70%): This is the most critical component in the formula. Its high proportion ensures that there is enough curing agent to participate in the reaction to achieve the best curing effect and physical properties.
[0107] 3. Parameter requirements of N3390 curing agent
[0108] NCO content (19.6% ± 0.3%): indicates that it has sufficient isocyanate groups to participate in the reaction with the hydroxyl groups in the coating, which is the key to ensure that the coating hardens and forms a strong structure.
[0109] Non-volatile components (90% ± 1%): High non-volatile components indicate the effectiveness of the curing agent in the coating, ensuring that the coating maintains high performance after curing.
[0110] Viscosity (550±150mPa.s): Moderate viscosity helps the uniform distribution of the curing agent during stirring and application, and also affects the overall application performance of the coating.
[0111] Color value (≤40) and HDI monomer (<0.15%): These parameters guarantee the purity and color of the curing agent and are critical to the appearance and performance of the final coating.
[0112] This combination of hardener and solvent helps to achieve the high performance requirements of self-repairing, age-resistant automotive OEM clearcoats, ensuring that the coating is in optimal condition in terms of mechanical properties, chemical resistance and appearance.
[0113] In the process of preparing self-repairing anti-aging automotive original factory varnish, the selection and proportion of flow regulating solvents are crucial because they directly affect the coating's applicability, drying time and final surface quality. Here are the reasons why these specific solvents and their proportions are selected:
[0114] Selected solvent: Butyl acetate: Butyl acetate is a commonly used solvent with good solvency and moderate volatility. It can effectively dissolve resins and other additives, while its volatility helps control the drying speed of the coating, thereby avoiding surface defects caused by too fast drying of the coating.
[0115] Diacetone Alcohol: Diacetone alcohol has a low evaporation rate and is used to regulate the drying process of the coating. This solvent helps to keep the coating wet during application, helps improve the leveling of the coating, and reduces brush marks and orange peel.
[0116] Methyl isobutyl ketone: This is a strong solvent with good solubility for a variety of resins, especially when you need to improve the solubility of solvent mixtures. It also helps to adjust the viscosity of the coating, making the coating easier to apply.
[0117] Propylene glycol methyl ether acetate: It is mainly used to improve the fluidity and workability of the coating. At the same time, its slow evaporation properties help to improve the overall surface quality of the coating.
[0118] Ratio selection: Butyl acetate: 50-60%: As the main solvent, it occupies a higher proportion to ensure sufficient dissolving power and moderate volatilization speed.
[0119] Diacetone alcohol: 15-20%: The lower volatilization rate helps to extend the open time of the coating, making it easier to operate during construction and improving the film-forming properties of the coating.
[0120] Methyl isobutyl ketone: 15-25%: Provides necessary solvency, especially for some insoluble resin components, to ensure the homogeneity of the mixture.
[0121] Propylene glycol methyl ether acetate: 10-15%: Adjusts the fluidity and drying characteristics of the final coating, making the coating smoother and reducing construction defects.
[0122] This ratio configuration is designed to balance the construction performance and drying characteristics of the coating to ensure that the coating has good appearance and performance. Through such a configuration, the drying rate of the coating and the final surface treatment effect can be effectively controlled, so that the coating can not only achieve the expected physical and chemical properties, but also show good operability and adaptability during the construction process.
[0123] In the preparation of self-healing, weather-resistant automotive OEM clearcoats, the ratio of the ingredients is critical to the performance of the final product. The weight ratios mentioned here (base paint: enhanced curing agent mixture: flow regulating solvent are 3:1:0.2-0.5) have been carefully designed to ensure that the coating has excellent performance and handling characteristics.
[0124] 1. The ratio of base paint and strengthening curing agent mixture (3:1):
[0125] The base paint contains self-healing PU resin, solvent-based self-healing resin and added functional agents (such as UV absorbers, light stabilizers, etc.), which are the basis of coating performance. A high proportion of base paint ensures that the coating has sufficient mechanical properties and self-healing ability.
[0126] The main function of the strengthening curing agent is to form a cross-linking network by reacting with the resin component in the base paint, thereby improving the durability and anti-aging performance of the coating. The ratio of 1:3 is sufficient to ensure that the resin in the base paint is fully cured without over-curing and causing brittle coating.
[0127] 2. Strengthen the ratio of curing agent mixture to flow regulating solvent (1:0.2-0.5):
[0128] Flow regulating solvents are added to adjust the viscosity and fluidity of the coating, making it easier to handle during application and helping the coating maintain a good surface condition before curing to reduce defects. The proportion of flow regulating solvent is relatively low to ensure that it does not over-thin the coating, thereby affecting the structural integrity and performance of the coating.
[0129] By precisely controlling the ratio of the hardener to the flow regulating solvent, it is possible to ensure that the hardener is evenly distributed in the coating while maintaining the appropriate viscosity of the coating during application and curing, avoiding application problems or performance degradation caused by excessively high or low viscosity.
[0130] This weight ratio design takes into account the comprehensive performance requirements of the coating, including mechanical strength, self-healing ability, aging resistance and ease of construction. The base paint provides the necessary resin base and functional additives, the reinforcing curing agent ensures that these resins can effectively cure to form a solid network structure, and the flow regulating solvent ensures that the coating has good construction performance and surface quality. This balance of proportions is optimized through experiments and feedback from actual applications to ensure that the final product achieves the best balance in performance and application effect.
[0131] In the preparation method of self-repairing anti-aging automotive original varnish, setting a specific stirring time and speed is essential to ensure the thoroughness of the chemical reaction and the homogeneity of the mixture. The following is a detailed explanation of why the stirring time and speed are set in this way:
[0132] The first stage (S1): stirring speed: 200-300r / min, stirring time: 30-40 minutes; in the initial stage, the stirring speed is slow and the time is long to ensure that the graphene can be fully dispersed in the solvent, while avoiding graphene damage or excessive shear force caused by too fast stirring.
[0133] Stage 2: Stirring speed: 300-400r / min, stirring time: 20-25 minutes; The stirring speed needs to be slightly increased at this stage because the addition of surfactants requires a strong shear force to help the surfactants evenly coat the surface of graphene. A shorter stirring time is sufficient to achieve this while avoiding changes in physical properties that may be caused by excessive stirring.
[0134] Stage 3: Stirring speed: 700-900r / min, stirring time: 20-25 minutes; after adding the dispersant, a higher stirring speed is required to promote full interaction and uniform distribution of the dispersant and graphene. High-speed stirring helps break up any residual agglomerates and ensures the effectiveness of the dispersant, thereby improving the quality of the final product.
[0135] The third step (S3): each stirring speed: 300-400r / min, stirring time: 5-10 minutes; the third stirring speed: 800-1000r / min; the initial two stirrings use a lower speed and a shorter time to ensure that the components in the base paint can be fully mixed without generating bubbles or excessive foam. The last stirring speed is increased to ensure thorough mixing and uniformity after adding all chemicals, especially when adding components with higher viscosity and requiring uniform distribution.
[0136] The fourth step (S4): the first stirring speed is 300-400r / min, and the time is 5-10 minutes; the second stirring speed is 600-800r / min, and the time is 10-20 minutes; the increasing stirring speed and time are to ensure that the strengthening curing agent mixture obtains appropriate shear force at different stages, thereby improving the uniformity and effectiveness of the reaction.
[0137] In summary, these stirring speeds and times are set based on the physical and chemical properties of the materials and the requirements of the reaction, with the goal of optimizing the mixing, dispersion and chemical reaction processes to obtain a final product with excellent properties. Precise control of these parameters is critical to ensuring the performance, appearance and durability of the final automotive OEM clearcoat.
[0138] Compared with the prior art, the preparation method of the self-repairing anti-aging automobile original varnish has the following beneficial effects:
[0139] 1. Enhanced self-repairing ability: The present invention uses L-2960 self-repairing PU resin and TRE-2-S2 solvent-based self-repairing resin. These resins have excellent self-repairing functions and can automatically repair after microscopic damage occurs without external intervention. Graphene is not only used as an enhancer in the present invention, but also has the function of converting solar energy into thermal energy. This ability enables graphene to accelerate the thermodynamic reaction of the surrounding self-repairing resin when receiving sunlight, thereby promoting the rapid recovery of the damaged area. This process fully utilizes natural energy, reduces the demand for additional energy supply, and enhances the environmental adaptability and energy efficiency of the coating.
[0140] 2. Improved mechanical properties: Through the three-stage graphene surface modification treatment and subsequent refinement process, the resulting graphene dispersion can be evenly distributed in the resin matrix, effectively improving the mechanical properties of the coating, including hardness, toughness and scratch resistance.
[0141] 3. Improved aging resistance: The use of graphene, UV absorbers (Tinuvin 1130) and light stabilizers (Tinuvin 292) further enhances the aging resistance of the coating. These additives can effectively absorb and disperse UV rays, reduce chemical degradation caused by UV radiation, and protect the coating from oxidation and photoaging. As a result, this coating has a longer outdoor service life and better color retention.
[0142] 4. Excellent surface properties: EFKA-3600 additives and EFKA FL 3750 leveling agent are used to improve the surface flatness and aesthetics of the coating. These additives can effectively control the fluidity and self-leveling of the coating during construction and reduce the generation of bubbles and shrinkage cavities.
[0143] In summary, the preparation method of the self-repairing and aging-resistant automobile original varnish of the present invention not only provides a high-performance and high-durability automobile coating solution, but also significantly improves the service life and economy of the automobile coating through its self-repairing and aging-resistant properties, bringing significant technological progress and economic benefits to the automobile manufacturing and maintenance industries. DETAILED DESCRIPTION
[0144] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments. Specific embodiment one:
[0146] A method for preparing a self-repairing, anti-aging automobile original varnish comprises the following steps:
[0147] S1 Three-stage graphene surface modification treatment: First stage: put the mixed solvent into the constant temperature device, add graphene, start the constant temperature device, set the temperature of the constant temperature device to 60-70℃; use a magnetic stirring device to carry out the first stirring operation;
[0148] The mixed solvent includes N-methylpyrrolidone, butyl acetate and diethylene glycol butyl ether; according to the weight ratio, N-methylpyrrolidone: butyl acetate: diethylene glycol butyl ether is 55:25:20;
[0149] The graphene is a single-layer graphene powder, the graphene single-layer rate is not less than 80%, the graphene diameter D50 is 5-10μm, the graphene purity is not less than 99%, the graphene defect density ratio is not more than 0.3, the graphene carbon oxygen ratio is not less than 25; the graphene specific surface area is not less than 2630m 2 / g;
[0150] The second stage: after the first stirring operation is completed, a surfactant is added and a second stirring is continued using a magnetic stirring device; the surfactant is phospholipid-polyethylene glycol-silane;
[0151] The third stage: after the second stirring operation is completed, the dispersant is added dropwise by a peristaltic pump, and the third stirring operation is continued by a magnetic stirring device. After the stirring is completed, a modified graphene mixture is obtained; the dispersant is specifically SUP1360 super dispersant;
[0152] According to the weight ratio, the mixed solvent: graphene: surfactant: hyperdispersant is 97:1:0.5:1.5;
[0153] In the first stirring operation, the stirring speed was 300 r / min and the stirring time was 30 minutes; in the second stirring operation, the stirring speed was 400 r / min and the stirring time was 20 minutes; in the third stirring operation, the stirring speed was 900 r / min and the stirring time was 20 minutes.
[0154] S2 refinement: placing the modified graphene mixture in a vertical ball mill, adding ball milling media, and starting ball milling. During the ball milling process, sampling is performed to detect the particle size until D50 ≤ 2 μm, thereby obtaining a graphene dispersion;
[0155] The operating speed of the grinding device is 1800 r / min, the grinding time is 100 minutes, the grinding medium is stainless steel beads, and the diameter of the grinding medium is 0.8 mm.
[0156] S3: preparing a base paint: according to the weight ratio, ethylene glycol butyl ether, n-butanol and propylene glycol methyl ether acetate are put into a mixer to perform a first stirring operation. After the first stirring operation, the self-healing PU resin and the solvent-based self-healing resin are sequentially added to perform a second stirring operation. After the second stirring operation is completed, the stirring speed is increased to perform a third stirring operation. During the stirring process of the third stirring operation, graphene dispersion, ultraviolet light absorber, light stabilizer, anti-shrinkage flow control agent, leveling agent and conductive agent are sequentially added to perform a fourth stirring operation. After stirring evenly, a base paint is obtained;
[0157] According to the weight ratio, ethylene glycol butyl ether: n-butanol: propylene glycol methyl ether acetate: self-healing PU resin: solvent-based self-healing resin: graphene dispersion: ultraviolet light absorber: light stabilizer: anti-shrinkage flow control additive: leveling agent: conductive agent is 3.2:3.6:2:55:30:3:2:0.5:0.3:0.2:0.2;
[0158] In the first stirring operation, the stirring speed is 300r / min and the stirring time is 10 minutes; in the second stirring operation, the stirring speed is 300r / min and the stirring time is 10 minutes; in the third stirring operation, the stirring speed is 800r / min and the stirring time is 30 minutes;
[0159] L-2960 self-healing PU resin forms an interpenetrating network structure system through the cross-linking reaction between PU resin and isocyanate; the parameters are as follows: viscosity (CPa.s / 25℃, CPS): 30-120CPS; solid content: 55%±2%; OH value (solid): 130mgKOH / g; OH% (solid): 3.8; acid value (solid): 2-5mgKOH / g; the solvent is butyl acetate;
[0160] The parameters of TRE-2-S2 solvent-based self-healing resin are as follows: viscosity (25°C): 450mPa.s; hydroxyl acrylic resin solid content: 70%; hydroxyl value: 116mgKOH / g; solvent: butyl acetate;
[0161] Tinuvin 1130 UV absorber parameters are as follows: ingredients include benzotriazole; dynamic viscosity at 20°C is 7400mPa.s; density at 20°C is 1.17g / cm 3 ;
[0162] The parameters of Tinuvin292 light stabilizer are as follows: the ingredients include 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and bis(1,2,2,6,6-pentamethylpiperidinol) sebacate; the dynamic viscosity at 20°C is 400cps; the density at 20°C is 1.02kg / m 3 ;
[0163] The ingredients of EFKA-3600 additive are 100% fluorocarbon molecular compounds;
[0164] The composition of EFKA FL 3750 leveling agent is 100% acrylate copolymer;
[0165] The parameters of BYK ES80 conductive agent are as follows: ingredient composition: alkyl alcohol ammonium salt solution of unsaturated carboxylic acid ester; amine value: 140 mgKOH / g; acid value: 140 mgKOH / g; density (20°C): 1.01 g / ml; solvent: isobutanol.
[0166] S4: preparing a strengthening curing agent: adding butyl acetate, methyl isobutyl ketone, and propylene glycol methyl ether acetate to a mixer in sequence to perform a first stirring operation; after the first stirring operation is completed, adding N3390 curing agent, and performing a second stirring operation, after the second stirring operation is completed, a strengthening curing agent mixture is obtained;
[0167] According to the weight ratio, butyl acetate: methyl isobutyl ketone: propylene glycol methyl ether acetate: N3390 curing agent is 15:12:8:65;
[0168] In the first stirring operation, the stirring speed is 300 r / min and the stirring time is 10 minutes; in the second stirring operation, the stirring speed is 800 r / min and the stirring time is 10 minutes.
[0169] The parameters of N3390 curing agent are as follows: type: hexamethylene diisocyanate trimer; supply form: 90% butyl acetate / 100 solvent naphtha (1:1) solution; NCO content: 19.6%±0.3%; non-volatile component: 90%±1%; viscosity: 550±150mPa.s; color value at 23℃≤40; HDI monomer<0.15%.
[0170] S5: preparing a flow regulating solvent: adding butyl acetate, diacetone alcohol, methyl isobutyl ketone and propylene glycol methyl ether acetate into a mixer and stirring them to obtain a flow regulating solvent after stirring them evenly;
[0171] According to the weight ratio, butyl acetate: diacetone alcohol: methyl isobutyl ketone: propylene glycol methyl ether acetate is 50:20:20:10;
[0172] S6 homogenization: mixing and stirring the base paint, the strengthening curing agent mixture and the flow regulating solvent to obtain the original automobile varnish;
[0173] According to the weight ratio, the base paint: the strengthening curing agent mixture: the flow regulating solvent is 3:1:0.2. Specific embodiment 2:
[0175] A method for preparing a self-repairing, anti-aging automobile original varnish comprises the following steps:
[0176] S1 Three-stage graphene surface modification treatment: First stage: put the mixed solvent into the constant temperature device, add graphene, start the constant temperature device, set the temperature of the constant temperature device to 60-70℃; use a magnetic stirring device to carry out the first stirring operation;
[0177] The mixed solvent includes N-methylpyrrolidone, butyl acetate and diethylene glycol butyl ether; according to the weight ratio, N-methylpyrrolidone: butyl acetate: diethylene glycol butyl ether is 60:20:20;
[0178] The graphene is a single-layer graphene powder, the graphene single-layer rate is not less than 80%, the graphene diameter D50 is 5-10 μm, the graphene purity is not less than 99%, the graphene defect density ratio is not greater than 0.3, the graphene carbon-oxygen ratio is not less than 25; the graphene specific surface area is not less than 2630. The second stage: after the first stirring operation is completed, a surfactant is added, and a magnetic stirring device is continued to be used for the second stirring; the surfactant is phospholipid-polyethylene glycol-silane;
[0179] The third stage: after the second stirring operation is completed, the dispersant is added dropwise by a peristaltic pump, and the third stirring operation is continued by a magnetic stirring device. After the stirring is completed, a modified graphene mixture is obtained; the dispersant is specifically SUP1360 super dispersant;
[0180] According to the weight ratio, the mixed solvent: graphene: surfactant: hyperdispersant is 96:1:1:2;
[0181] In the first stirring operation, the stirring speed was 300 r / min and the stirring time was 40 minutes; in the second stirring operation, the stirring speed was 400 r / min and the stirring time was 25 minutes; in the third stirring operation, the stirring speed was 900 r / min and the stirring time was 20 minutes.
[0182] S2 refinement: placing the modified graphene mixture in a vertical ball mill, adding ball milling media, and starting ball milling. During the ball milling process, sampling is performed to detect the particle size until D50 ≤ 2 μm, thereby obtaining a graphene dispersion;
[0183] The operating speed of the grinding device is 2000 r / min, the grinding time is 90 minutes, the grinding medium is ceramic beads, and the grinding medium diameter is 1.2 mm.
[0184] S3: preparing a base paint: according to the weight ratio, ethylene glycol butyl ether, n-butanol and propylene glycol methyl ether acetate are put into a mixer to perform a first stirring operation. After the first stirring operation, the self-healing PU resin and the solvent-based self-healing resin are sequentially added to perform a second stirring operation. After the second stirring operation is completed, the stirring speed is increased to perform a third stirring operation. During the stirring process of the third stirring operation, graphene dispersion, ultraviolet light absorber, light stabilizer, anti-shrinkage flow control agent, leveling agent and conductive agent are sequentially added to perform a fourth stirring operation. After stirring evenly, a base paint is obtained;
[0185] According to the weight ratio, ethylene glycol butyl ether: n-butanol: propylene glycol methyl ether acetate: self-healing PU resin: solvent-based self-healing resin: graphene dispersion: ultraviolet light absorber: light stabilizer: anti-shrinkage flow control agent: leveling agent: conductive agent is 4.8:4:1:60:25:2:1:2:0.5:0.3:0.2;
[0186] In the first stirring operation, the stirring speed is 300r / min and the stirring time is 8 minutes; in the second stirring operation, the stirring speed is 300r / min and the stirring time is 10 minutes; in the third stirring operation, the stirring speed is 1000r / min and the stirring time is 20 minutes;
[0187] L-2960 self-healing PU resin forms an interpenetrating network structure system through the cross-linking reaction between PU resin and isocyanate; the parameters are as follows: viscosity (CPa.s / 25℃, CPS): 30-120CPS; solid content: 55%±2%; OH value (solid): 130mgKOH / g; OH% (solid): 3.8; acid value (solid): 2-5mgKOH / g; the solvent is butyl acetate;
[0188] The parameters of TRE-2-S2 solvent-based self-healing resin are as follows: viscosity (25°C): 450mPa.s; hydroxyl acrylic resin solid content: 70%; hydroxyl value: 116mgKOH / g; solvent: butyl acetate;
[0189] Tinuvin 1130 UV absorber parameters are as follows: ingredients include benzotriazole; dynamic viscosity at 20°C is 7400mPa.s; density at 20°C is 1.17g / cm 3 ;
[0190] The parameters of Tinuvin292 light stabilizer are as follows: the ingredients include 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and bis(1,2,2,6,6-pentamethylpiperidinol) sebacate; the dynamic viscosity at 20°C is 400cps; the density at 20°C is 1.02kg / m 3 ;
[0191] The ingredients of EFKA-3600 additive are 100% fluorocarbon molecular compounds;
[0192] The composition of EFKA FL 3750 leveling agent is 100% acrylate copolymer;
[0193] The parameters of BYK ES80 conductive agent are as follows: ingredient composition: alkyl alcohol ammonium salt solution of unsaturated carboxylic acid ester; amine value: 140 mgKOH / g; acid value: 140 mgKOH / g; density (20°C): 1.01 g / ml; solvent: isobutanol.
[0194] S4: preparing a strengthening curing agent: adding butyl acetate, methyl isobutyl ketone, and propylene glycol methyl ether acetate to a mixer in sequence to perform a first stirring operation; after the first stirring operation is completed, adding N3390 curing agent, and performing a second stirring operation, after the second stirring operation is completed, a strengthening curing agent mixture is obtained;
[0195] According to the weight ratio, butyl acetate: methyl isobutyl ketone: propylene glycol methyl ether acetate: N3390 curing agent is 20:10:10:60;
[0196] In the first stirring operation, the stirring speed is 300 r / min and the stirring time is 10 minutes; in the second stirring operation, the stirring speed is 600 r / min and the stirring time is 10 minutes.
[0197] The parameters of N3390 curing agent are as follows: type: hexamethylene diisocyanate trimer; supply form: 90% butyl acetate / 100 solvent naphtha (1:1) solution; NCO content: 19.6%±0.3%; non-volatile component: 90%±1%; viscosity: 550±150mPa.s; color value at 23℃≤40; HDI monomer<0.15%.
[0198] S5: preparing a flow regulating solvent: adding butyl acetate, diacetone alcohol, methyl isobutyl ketone and propylene glycol methyl ether acetate into a mixer and stirring them to obtain a flow regulating solvent after stirring them evenly;
[0199] According to the weight ratio, butyl acetate: diacetone alcohol: methyl isobutyl ketone: propylene glycol methyl ether acetate is 60:15:15:10;
[0200] S6 homogenization: after the base paint, the strengthening curing agent mixture and the flow regulating solvent are mixed and stirred evenly, the original automobile varnish is obtained; the speed is set to 300r / min and stirred for 5 minutes;
[0201] According to the weight ratio, the base paint: the strengthening curing agent mixture: the flow regulating solvent is 3:1:0.3. Specific embodiment three:
[0203] A method for preparing a self-repairing, anti-aging automobile original varnish comprises the following steps:
[0204] S1 Three-stage graphene surface modification treatment: First stage: put the mixed solvent into the constant temperature device, add graphene, start the constant temperature device, set the temperature of the constant temperature device to 60-70℃; use a magnetic stirring device to carry out the first stirring operation;
[0205] The mixed solvent includes N-methylpyrrolidone, butyl acetate and diethylene glycol butyl ether; according to the weight ratio, N-methylpyrrolidone: butyl acetate: diethylene glycol butyl ether is 50:20:30;
[0206] The graphene is a single-layer graphene powder, the graphene single-layer rate is not less than 80%, the graphene diameter D50 is 5-10μm, the graphene purity is not less than 99%, the graphene defect density ratio is not more than 0.3, the graphene carbon oxygen ratio is not less than 25; the graphene specific surface area is not less than 2630m 2 / g;
[0207] The second stage: after the first stirring operation is completed, a surfactant is added and a second stirring is continued using a magnetic stirring device; the surfactant is phospholipid-polyethylene glycol-silane;
[0208] The third stage: after the second stirring operation is completed, the dispersant is added dropwise by a peristaltic pump, and the third stirring operation is continued by a magnetic stirring device. After the stirring is completed, a modified graphene mixture is obtained; the dispersant is specifically SUP1360 super dispersant;
[0209] According to the weight ratio, the mixed solvent: graphene: surfactant: hyperdispersant is 98:0.5:0.5:1;
[0210] In the first stirring operation, the stirring speed was 300 r / min and the stirring time was 40 minutes; in the second stirring operation, the stirring speed was 400 r / min and the stirring time was 25 minutes; in the third stirring operation, the stirring speed was 900 r / min and the stirring time was 25 minutes.
[0211] S2 refinement: placing the modified graphene mixture in a vertical ball mill, adding ball milling media, and starting ball milling. During the ball milling process, sampling is performed to detect the particle size until D50 ≤ 2 μm, thereby obtaining a graphene dispersion;
[0212] The operating speed of the grinding device is 2000 r / min, the grinding time is 80 minutes, the grinding medium is stainless steel beads, and the grinding medium diameter is 0.8 mm.
[0213] S3: preparing a base paint: according to the weight ratio, ethylene glycol butyl ether, n-butanol and propylene glycol methyl ether acetate are put into a mixer to perform a first stirring operation. After the first stirring operation, the self-healing PU resin and the solvent-based self-healing resin are sequentially added to perform a second stirring operation. After the second stirring operation is completed, the stirring speed is increased to perform a third stirring operation. During the stirring process of the third stirring operation, graphene dispersion, ultraviolet light absorber, light stabilizer, anti-shrinkage flow control agent, leveling agent and conductive agent are sequentially added to perform a fourth stirring operation. After stirring evenly, a base paint is obtained;
[0214] According to the weight ratio, ethylene glycol butyl ether: n-butanol: propylene glycol methyl ether acetate: self-healing PU resin: solvent-based self-healing resin: graphene dispersion: ultraviolet light absorber: light stabilizer: anti-shrinkage flow control agent: leveling agent: conductive agent is 2:2.3:2:50:35:4:3:1:0.3:0.2:0.2;
[0215] In the first stirring operation, the stirring speed is 400r / min and the stirring time is 10 minutes; in the second stirring operation, the stirring speed is 400r / min and the stirring time is 10 minutes; in the third stirring operation, the stirring speed is 1000r / min and the stirring time is 20 minutes;
[0216] L-2960 self-healing PU resin forms an interpenetrating network structure system through the cross-linking reaction between PU resin and isocyanate; the parameters are as follows: viscosity (CPa.s / 25℃, CPS): 30-120CPS; solid content: 55%±2%; OH value (solid): 130mgKOH / g; OH% (solid): 3.8; acid value (solid): 2-5mgKOH / g; the solvent is butyl acetate;
[0217] The parameters of TRE-2-S2 solvent-based self-healing resin are as follows: viscosity (25°C): 450mPa.s; hydroxyl acrylic resin solid content: 70%; hydroxyl value: 116mgKOH / g; solvent: butyl acetate;
[0218] Tinuvin 1130 UV absorber parameters are as follows: ingredients include benzotriazole; dynamic viscosity at 20°C is 7400mPa.s; density at 20°C is 1.17g / cm 3 ;
[0219] The parameters of Tinuvin292 light stabilizer are as follows: the ingredients include 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and bis(1,2,2,6,6-pentamethylpiperidinol) sebacate; the dynamic viscosity at 20°C is 400cps; the density at 20°C is 1.02kg / m 3 ;
[0220] The ingredients of EFKA-3600 additive are 100% fluorocarbon molecular compounds;
[0221] The composition of EFKA FL 3750 leveling agent is 100% acrylate copolymer;
[0222] The parameters of BYK ES80 conductive agent are as follows: ingredient composition: alkyl alcohol ammonium salt solution of unsaturated carboxylic acid ester; amine value: 140 mgKOH / g; acid value: 140 mgKOH / g; density (20°C): 1.01 g / ml; solvent: isobutanol.
[0223] S4: preparing a strengthening curing agent: adding butyl acetate, methyl isobutyl ketone, and propylene glycol methyl ether acetate to a mixer in sequence to perform a first stirring operation; after the first stirring operation is completed, adding N3390 curing agent, and performing a second stirring operation, after the second stirring operation is completed, a strengthening curing agent mixture is obtained;
[0224] According to the weight ratio, butyl acetate: methyl isobutyl ketone: propylene glycol methyl ether acetate: N3390 curing agent is 15:10:5:70;
[0225] In the first stirring operation, the stirring speed is 400 r / min and the stirring time is 10 minutes; in the second stirring operation, the stirring speed is 800 r / min and the stirring time is 20 minutes.
[0226] The parameters of N3390 curing agent are as follows: type: hexamethylene diisocyanate trimer; supply form: 90% butyl acetate / 100 solvent naphtha (1:1) solution; NCO content: 19.6%±0.3%; non-volatile component: 90%±1%; viscosity: 550±150mPa.s; color value at 23℃≤40; HDI monomer<0.15%.
[0227] S5: preparing a flow regulating solvent: adding butyl acetate, diacetone alcohol, methyl isobutyl ketone and propylene glycol methyl ether acetate into a mixer and stirring them to obtain a flow regulating solvent after stirring them evenly;
[0228] In terms of weight ratio, butyl acetate: diacetone alcohol: methyl isobutyl ketone: propylene glycol methyl ether acetate is 55:15:15:15;
[0229] Set the speed to 300r / min and stir for 10 minutes;
[0230] S6 homogenization: after the base paint, the strengthening curing agent mixture and the flow regulating solvent are mixed and stirred evenly, the original automobile varnish is obtained; the speed is set to 300r / min and stirred for 10 minutes;
[0231] According to the weight ratio, the base paint: the strengthening curing agent mixture: the flow regulating solvent is 3:1:0.3.
[0232] The original automobile varnish prepared in specific examples 1-3 was sprayed by an automatic spray gun, and the parameters of the automatic spray gun were set as follows: the air pressure was 3-3.5KG / CM2, the spraying thickness was 10-15μm, and the sprayed products were placed in an oven at 140°C and baked in the oven for 30 minutes to achieve the curing of the coating. After the curing was completed, the products were taken out of the oven and cooled to room temperature to obtain the cured products. The performance of the cured products was tested, as shown in Table 1:
[0233]
[0234]
[0235]
[0236] Table 1
[0237] By analyzing the data in Table 1, it can be seen that the self-repairing and aging-resistant original automobile varnish of the present invention has excellent performance and can meet the standards of original automobile paint.
[0238] The self-repairing anti-aging automobile original varnish cured samples prepared in specific examples 1-3 were scratched (without cracks) and placed outdoors under sunlight, numbered 1, 2 and 3 respectively;
[0239]
[0240]
[0241] Table 2
[0242] The specific embodiments described herein are merely illustrative of the spirit of the invention. A person skilled in the art of the invention may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but will not deviate from the spirit of the invention or exceed the defined scope. It should be understood that within the scope of the following claims, ordinary technicians may make changes and modifications. Specifically, the present invention encompasses additional embodiments with any combination of features from the above-mentioned different embodiments. With respect to the use of the expression "generally" or "substantially", this patent application should be understood to disclose that these features and values are also fully satisfied, i.e., there is no aforementioned characterization as "generally" or "substantially".
Claims
1. A method for preparing a self-repairing and aging-resistant automobile original varnish, characterized in that: The preparation method of the self-repairing anti-aging automobile original factory varnish comprises the following steps: S1 Three-stage graphene surface modification treatment: First stage: put the mixed solvent into the constant temperature device, add graphene, start the constant temperature device, set the temperature of the constant temperature device to 60-70℃; use a magnetic stirring device to carry out the first stirring operation; The mixed solvent includes N-methylpyrrolidone, butyl acetate and diethylene glycol butyl ether; according to the weight ratio, N-methylpyrrolidone: butyl acetate: diethylene glycol butyl ether is 50-60: 20-30: 20-30; The graphene is a single-layer graphene powder, the graphene single-layer rate is not less than 80%, the graphene diameter D50 is 5-10μm, the graphene purity is not less than 99%, the graphene defect density ratio is not more than 0.3, the graphene carbon oxygen ratio is not less than 25; the graphene specific surface area is not less than 2630m 2 / g; The second stage: after the first stirring operation is completed, a surfactant is added and a second stirring is continued using a magnetic stirring device; the surfactant is phospholipid-polyethylene glycol-silane; The third stage: after the second stirring operation is completed, the dispersant is added dropwise by a peristaltic pump, and the third stirring operation is continued by a magnetic stirring device. After the stirring is completed, a modified graphene mixture is obtained; the dispersant is specifically SUP1360 super dispersant; According to the weight ratio, the mixed solvent: graphene: surfactant: hyperdispersant is 96-98: 0.5-1: 0.5-1: 1-2; S2 refinement: placing the modified graphene mixture in a ball mill, adding ball milling media, and starting ball milling. During the ball milling process, sampling is performed to detect the particle size until D50 ≤ 2 μm, thereby obtaining a graphene dispersion. S3 prepares the base paint: according to the weight ratio, ethylene glycol butyl ether, n-butanol and propylene glycol methyl ether acetate are put into the mixer to carry out the first stirring operation. After the first stirring operation, the self-repairing PU resin and the solvent-based self-repairing resin are added in sequence to carry out the second stirring operation. After the second stirring operation is completed, the stirring speed is increased to carry out the third stirring operation. During the stirring process of the third stirring operation, the graphene dispersion, the ultraviolet light absorber, the light stabilizer, the anti-shrinkage flow control agent, the leveling agent are added in sequence. The agent and the conductive agent are stirred for the fourth time, and after stirring evenly, a base paint is obtained; according to the weight ratio, ethylene glycol butyl ether: n-butanol: propylene glycol methyl ether acetate: self-repairing PU resin: solvent-based self-repairing resin: graphene dispersion: ultraviolet light absorber: light stabilizer: anti-shrinkage flow control additive: leveling agent: conductive agent is 2-5:2-5:1-3:50-60:25-35:2-4:1-3:0.5-1:0.2-0.3:0.2-0.3:0.2-0.3; The self-repairing PU resin is specifically L-2960 self-repairing PU resin; the solvent-based self-repairing resin is specifically TRE-2-S2 solvent-based self-repairing resin; the ultraviolet light absorber is specifically Tinuvin 1130 ultraviolet light absorber; the light stabilizer is specifically Tinuvin 292 light stabilizer; the anti-shrinkage flow control additive is specifically EFKA-3600 additive; the leveling agent is specifically EFKA FL3750 leveling agent; the conductive agent is specifically BYK ES80 conductive agent; S4: preparing a strengthening curing agent: adding butyl acetate, methyl isobutyl ketone, and propylene glycol methyl ether acetate to a mixer in sequence to perform a first stirring operation; after the first stirring operation is completed, adding N3390 curing agent, and performing a second stirring operation, after the second stirring operation is completed, a strengthening curing agent mixture is obtained; According to the weight ratio, butyl acetate: methyl isobutyl ketone: propylene glycol methyl ether acetate: N3390 curing agent is 15-20: 10-15: 5-10: 60-70; S5: preparing a flow regulating solvent: adding butyl acetate, diacetone alcohol, methyl isobutyl ketone and propylene glycol methyl ether acetate into a mixer and stirring them to obtain a flow regulating solvent after stirring them evenly; According to the weight ratio, butyl acetate: diacetone alcohol: methyl isobutyl ketone: propylene glycol methyl ether acetate is 50-60: 15-20: 15-25: 10-15; S6 homogenization: mixing and stirring the base paint, the strengthening curing agent mixture and the flow regulating solvent to obtain the original automobile varnish; According to the weight ratio, the base paint: the strengthening curing agent mixture: the flow regulating solvent is 3:1:0.2-0.
5.
2. The method for preparing the self-repairing anti-aging automobile original varnish according to claim 1, characterized in that: In step S1, in the first stirring operation, the stirring speed is 200-300 r / min, and the stirring time is 30-40 minutes; In the second stirring operation, the stirring speed is 300-400r / min, and the stirring time is 20-25 minutes; in the third stirring operation, the stirring speed is 700-900r / min, and the stirring time is 20-25 minutes; The parameters of SUP1360 hyperdispersant are as follows: ingredient composition: polymer block copolymer solution; effective content: 80%±2%; solvent: N-methylpyrrolidone.
3. The method for preparing the self-repairing anti-aging automobile original varnish according to claim 1, characterized in that: In step S2, the ball mill is specifically a vertical ball mill, the operating speed of the vertical ball mill is 1800-2000r / min, the ball milling medium is any one of stainless steel beads, ceramic beads and cemented carbide beads, and the diameter of the ball milling medium is 0.8-1.2mm.
4. The method for preparing the self-repairing anti-aging automobile original varnish according to claim 1, characterized in that: In step S3, in the first stirring operation, the stirring speed is 300-400 r / min, and the stirring time is 5-10 minutes; in the second stirring operation, the stirring speed is 300-400 r / min, and the stirring time is 5-10 minutes; in the third stirring operation, the stirring speed is 800-1000 r / min.
5. The method for preparing the self-repairing anti-aging automobile original varnish according to claim 1, characterized in that: In step S3, the parameters of L-2960 self-repairing PU resin are as follows: viscosity (CPa.s / 25°C, CPS): 30-120 CPS; solid content: 55% ± 2%; OH value (solid): 130 mgKOH / g; OH% (solid): 3.8; acid value (solid): 2-5 mgKOH / g; the solvent is butyl acetate; The parameters of TRE-2-S2 solvent-based self-healing resin are as follows: viscosity (25°C): 450mPa.s; hydroxyl acrylic resin solid content: 70%; hydroxyl value: 116mgKOH / g; solvent: butyl acetate; Tinuvin 1130 UV absorber parameters are as follows: ingredients include benzotriazole; dynamic viscosity at 20°C is 7400mPa.s; density at 20°C is 1.17g / cm 3 ; The parameters of Tinuvin292 light stabilizer are as follows: Ingredients: 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and bis(1,2,2,6,6-pentamethylpiperidinol) sebacate; dynamic viscosity at 20°C is 400cps; density at 20°C is 1.02kg / m 3 ; The ingredients of EFKA-3600 additive are 100% fluorocarbon molecular compounds; The composition of EFKA FL 3750 leveling agent is 100% acrylate copolymer; The parameters of BYK ES80 conductive agent are as follows: ingredient composition: alkyl alcohol ammonium salt solution of unsaturated carboxylic acid ester; amine value: 140 mgKOH / g; acid value: 140 mgKOH / g; density (20°C): 1.01 g / ml; solvent: isobutanol.
6. The method for preparing the self-repairing anti-aging automobile original varnish according to claim 1, characterized in that: In step S4, in the first stirring operation, the stirring speed is 300-400 r / min, and the stirring time is 5-10 minutes; in the second stirring operation, the stirring speed is 600-800 r / min, and the stirring time is 10-20 minutes.
7. The method for preparing the self-repairing anti-aging automobile original varnish according to claim 1, characterized in that: In step S4, the parameters of N3390 curing agent are as follows: type: hexamethylene diisocyanate trimer; supply form: 90% butyl acetate / 100 solvent naphtha (1:1) solution; NCO content: 19.6%±0.3%; non-volatile components: 90%±1%; Viscosity: 550±150mPa.s; color value ≤40 at 23℃; HDI monomer <0.15%.
8. The method for preparing the self-repairing anti-aging automobile original varnish according to claim 1, characterized in that: In the stirring operation in step S5, the stirring speed is 300-400 r / min, and the stirring time is 5-10 minutes.